Mixing performance test and uniformity analysis of a two-stage injection jet on-line mixer - Ping Jiang; Siliang Xiang; Wenwu Hu; Yahui Luo; Wen Li; Xiang Dong; Yixin Shi (PLoS ONE, 2025)
With the mixing of water and pesticides being a critical step, which is often performed using mixers. Traditional mixers, however, frequently exhibit issues such as uneven mixing and limited ratios. A dual-stage injection jet online mixer was designed to enhance the uniformity of pesticide and water mixing. This paper presents performance tests and uniformity analysis of this mixer, aiming to assess its effectiveness post-installation and to determine if it meets the required mixing performance and uniformity standards. Image analysis was utilized for qualitative assessment, revealing that the mixer’s two-dimensional curves in both axial and radial directions matched the pattern of pure pesticides. The root mean square error (RMSE) decreased with increasing mixing ratios, ranging from a minimum of 8.57% at a 300:1 ratio to a maximum of 9.94% at 2000:1. These variations were minimal, indicating good homogeneity across different ratios. Quantitative analysis using UV spectrophotometry showed that the actual mass concentration of the mixture deviated by less than 0.1% from the expected values at different sampling times, confirming superior temporal distribution uniformity. The variation in mixture mass concentration was insignificant across different locations, and the error variation at the same mixing ratio was less than 0.03%, indicating an excellent spatial distribution uniformity of the mixer. These findings demonstrate that the two-stage injection jet online mixer is effective over a wide range of mixing ratios, providing theoretical and technical support for accurate online variable spraying. This advancement is crucial for enhancing pesticide mixing efficiency and promoting sustainable agricultural development.